2019
DOI: 10.3390/ijerph16101868
|View full text |Cite
|
Sign up to set email alerts
|

Do Temporary Workers More Often Decide to Work While Sick? Evidence for the Link between Employment Contract and Presenteeism in Europe

Abstract: European employees are increasingly likely to work in cases of illness (sickness presenteeism, SP). Past studies found inconsistent evidence for the assumption that temporary workers decide to avoid taking sick leave due to job insecurity. A new measure to identify decision-based determinants of SP is presenteeism propensity (PP), which is the number of days worked while ill in relation to the sum of days worked while ill and days taken sickness absence. We investigated the link between employment contract and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
3
28
1
1
Order By: Relevance
“…Our results support previous studies that determined that over half of nurses have attended work despite being ill (Graf et al ; Warren et al ), which points to presenteeism as a phenomenon that must be analysed in depth due to its high prevalence (Chiu et al ; Mach et al ) and its proven association with labour discontent, work‐load, labour stress and insecurity (Reuter et al ; Skela‐Savic et al ). Its consequences have proven to be significant for the healthcare system and employees, showing that strategic training to control and reduce it is essential (Schneider et al ).…”
Section: Discussionsupporting
confidence: 91%
“…Our results support previous studies that determined that over half of nurses have attended work despite being ill (Graf et al ; Warren et al ), which points to presenteeism as a phenomenon that must be analysed in depth due to its high prevalence (Chiu et al ; Mach et al ) and its proven association with labour discontent, work‐load, labour stress and insecurity (Reuter et al ; Skela‐Savic et al ). Its consequences have proven to be significant for the healthcare system and employees, showing that strategic training to control and reduce it is essential (Schneider et al ).…”
Section: Discussionsupporting
confidence: 91%
“…Support for this explanation is found in studies observing increased presenteeism in context of occupational downsizing 1 and temporary employment. 29 One implication of the overall finding is that strategies aiming to reduce presenteeism must consider the role of labour market contexts. Notably, this may receive additional relevance in the near future, where economic consequences of the COVID-19 pandemic will result in raising unemployment rates worldwide, especially among those countries with less economic resources.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that there are significant differences in the incidences of absenteeism and presenteeism among OECD countries, and that the patterns of changes also vary among the countries (10,(16)(17)(18). To date, however, contextual explanations of the differences in the prevalence of absenteeism and presenteeism have been focused on unemployment and sickness benefits (7,9,16,19).…”
Section: Introductionmentioning
confidence: 99%